Public–Private Partnership Practices in the World and Türkiye: A Numerical Analysis - Recep Emre Eriçok (İktisat Politikası Araştırmaları Dergisi)
Nowadays, there is a growing consensus on the importance of infrastructure investments in terms of economic and social development. In this context, public-private partnerships are recognized as one of the most important instruments for supporting infrastructure investments. In Türkiye, public-private partnership practices have been utilized extensively in the execution of numerous projects for more than three decades. This study was designed to evaluate and analyze with numerical data the public-private partnership practices in the world and Türkiye within thecontext of global developments in the field of public-private partnership. First, the conceptual framework of publicprivate partnership was examined, and then numerical data on public-private partnership practices in the world andTürkiye were analyzed in light of the increasing infrastructure investment need. The study’s results show that Türkiye’spublic-private partnership practices differ from those of other countries, and that the public-private partnership governance framework, particularly the management and reporting of fiscal risks and fiscal transparency should be improved. Furthermore, the fiscal risks incurred due to contingent liabilities provided within the scope of publicprivate partnership projects have increased. To reduce fiscal risks and improve fiscal transparency in the field of publicprivate partnership, stakeholders must provide contingent liabilities in Turkish Lira rather than foreign currency and avoid long-term guarantees. Moreover, information on guarantees given by institutions that implement public-private partnership projects other than the Treasury should be shared with the public transparently and regularly. Alternatively,all guarantees should be gathered under a single institution and resources should be used effectively and converted into efficient investments and directed to priority sectors. If these objectives are met, it is anticipated that discussions on public-private partnerships in Türkiye will decrease, the potential contributions of these projects will be enhanced, and their positive contribution to Türkiye’s economic performance will increase.